Enormous smallness : a story of E. E. Cummings - Burgess, Matthew (Enchanted Lion Books, 2015)
"Enormous Smallness is a nonfiction picture book about the poet E. E. Cummings. Here E.E.'s life is presented in a way that will make children curious about him and will lead them to play with words and ask plenty of questions as well. Lively and informative, the book also presents some of Cummings's most wonderful poems, integrating them seamlessly into the story to give the reader the music of his voice and a spirited, sensitive introduction to his poetry."--Amazon.com.